1999
DOI: 10.1006/dbio.1999.9233
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics of the [Ca2+]iRise Induced by Microinjection of Sperm Extract into Mouse Eggs: Preferential Induction of a Ca2+Wave from the Cortex Mediated by the Inositol 1,4,5-Trisphosphate Receptor

Abstract: Hamster sperm extract (SE) possessing Ca2+ oscillation-inducing activity was microinjected into the peripheral or central region of mouse eggs, and the first increase in intracellular Ca2+ concentration ([Ca2+]i), together with the spread of fluorescence-labeled SE in the ooplasm, was investigated by imaging with confocal microscopy. Injection into the periphery always induced a Ca2+ wave that started from the injection site after a delay of 5 to 30 s depending on the concentration of SE. The diluted SE caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 37 publications
6
26
0
Order By: Relevance
“…Preparation of Eggs and [Ca 2ϩ ] i Measurement-Mature mouse eggs were obtained from the oviducts of B6D2F1 female mice superovulated by intraperitoneal injection of gonadotropins (8). They were loaded with the Ca 2ϩ -sensitive dye fura-2 (5 M; dextran, Molecular Probes Inc.) in M2 medium for 8 min at 37°C and then transferred to a plastic dish mounted on an inverted fluorescence microscope and heated at 30 -32°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of Eggs and [Ca 2ϩ ] i Measurement-Mature mouse eggs were obtained from the oviducts of B6D2F1 female mice superovulated by intraperitoneal injection of gonadotropins (8). They were loaded with the Ca 2ϩ -sensitive dye fura-2 (5 M; dextran, Molecular Probes Inc.) in M2 medium for 8 min at 37°C and then transferred to a plastic dish mounted on an inverted fluorescence microscope and heated at 30 -32°C.…”
Section: Methodsmentioning
confidence: 99%
“…Injection of recombinant PLC into mouse eggs induces Ca 2ϩ oscillations as well (7). The Ca 2ϩ oscillation-inducing activity of sperm extract (4,8) is lost when the extract is pretreated with an antibody against PLC (1). Thus, PLC is a strong candidate for the sperm-derived Ca 2ϩ oscillation-inducing protein.…”
Section: Plcmentioning
confidence: 99%
“…Interestingly, the ability of mammalian sperm extracts to trigger [Ca 2+ ] i oscillations extends to eggs across species (Figs. 1C and D) and even across phyla (Wilding et al, 1997;Wu et al, 1997;Oda et al, 1999;Parrington, et al, 1999;Dong et al, 2000;Jones et al, 2000;Stricker et al, 2000;Li et al, 2001;Coward et al, 2003). Moreover, these extracts are also able to trigger [Ca 2+ ] i oscillations in somatic cells (Berrie et al, 1996).…”
Section: Introductionmentioning
confidence: 93%
“…The appearance of cortical ER-rich domains during maturation correlates with an increase in Journal of Cell Science 115 (18) sensitivity to Ins(1,4,5)P3 and to sperm-induced Ca 2+ release (Chiba et al, 1990;Shiraishi et al, 1995;Mehlmann and Kline, 1994;Terasaki et al, 2001) (reviewed in Sardet et al, 2002). Local injections of Ins(1,4,5)P3 and sperm extracts in mouse eggs have revealed that the egg cortex is a region of higher sensitivity to Ins(1,4,5)P3 and to sperm extracts (Oda et al, 1999). Indeed, although the abundance of ER in the egg cortex renders this region more sensitive to Ins(1,4,5)P3, it is also exposed to the highest concentrations of Ins(1,4,5)P3 as it is closest to the source of PtdIns(4,5)P2 in the plasma membrane (Halet et al, 2002;Sardet et al, 2002).…”
Section: Ca 2+ Wave Pacemakers In Eggs Reside In Cortical Errich Domainsmentioning
confidence: 99%